ответ:
\frac{13k-4}{3-13k}+ \frac{x}{3-13k}=1
\frac{13k-4+x}{3-13k}= \frac{3-13k}{3-13k}
\frac{13k-4+x}{3-13k}- \frac{3-13k}{3-13k} =0
\frac{13k-4+x-(3-13k)}{3-13k}=0
\frac{13k-4+x-3+13k}{3-13k}=0
\frac{26k-7+x}{3-13k}=0
\left \{ {{26k-7+x=0} \atop {3-13k \neq 0}} \right. ; \left \{ {{x=-26k+7} \atop {k \neq \frac{3}{13} }} \right. ; \left \{ {{x=7-26k} \atop {k \neq \frac{3}{13} }} \right.
ответ: если k \neq \frac{3}{13} , то x=7-26k
объяснение:
Объяснение:
1.
a)5√2+2√32-√98= 5√2+2√(16*2)-√(49*2)= 5√2+2√(4²*2)-V(7²*2)=
=5√2+2*4√2-7√2= 5√2+8√2-7√2= 13√2-7√2=6√2
b)(4√3+2√21)*√3=4√3*√3+√27*√3=4√(3*3)=4√3²+√27*3)=4*3+√(81)= =12+√9²=12+9=21
c)(√5-√3)²=5-2√5*√3+3=5-√(2*18)+3=5-2√(3²)*2)+3=8-2*3√2=8-6√2
2.
1/2√28 i 1/3√54
√(1/2)²*28) i √(1/3²)*54)
√(1/4*28) i √(1/9)*54)
√7 > √6
3.
(√10 +5)/(2+√10) = (√10 +5)/(2+√10) *(2-√10)/(2-√10)=
=(√10+5)(2-√10) /(4-10)= (2√10-√10*√10+10-5√10)/(-6)=
=(-3√10-10+10)/(-6)=3√10/6=√10 / 2